An overview of Bangladesh Bureau of Statistics : focus on education household survey - Bhuiyan, Md. Tanjib Hassain (BRAC University, 2016)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Development Management and Practice, 2015.